2020
DOI: 10.1007/s00417-020-04637-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic power of scleral spur length in primary open-angle glaucoma

Abstract: Purpose To investigate the diagnostic capability of scleral spur length in discriminating eyes with primary open-angle glaucoma (POAG) from healthy eyes. Methods Seventy-eight eyes of 78 patients with POAG and 93 eyes of 93 age-, sex-and axial length-matched healthy subjects were included. The scleral spur length was measured using swept-source optical coherence tomography. Receiver operating characteristic (ROC) curves were derived based on the measurements. Results The scleral spur length was significantly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…The previous histological sections study by Swain DL et al found that the signi cantly shorter SS in POAG eyes than in age-matched normal eye, which could not provide su cient support for the SC and TM 10 . In addition, Li M et al also found the scleral spur length was signi cantly shorter in POAG eyes compared with healthy eyes by SS-OCT in real-time and in vivo 11 . These results suggest that the shorter SS than in normal eyes contains fewer ciliary muscle bers and TM attachments, circumferentially oriented collagenous and elastic bers, and circularly oriented and spindle-shaped cells.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The previous histological sections study by Swain DL et al found that the signi cantly shorter SS in POAG eyes than in age-matched normal eye, which could not provide su cient support for the SC and TM 10 . In addition, Li M et al also found the scleral spur length was signi cantly shorter in POAG eyes compared with healthy eyes by SS-OCT in real-time and in vivo 11 . These results suggest that the shorter SS than in normal eyes contains fewer ciliary muscle bers and TM attachments, circumferentially oriented collagenous and elastic bers, and circularly oriented and spindle-shaped cells.…”
Section: Discussionmentioning
confidence: 92%
“…2D): the SSL (the a-c solid line) was measured from the tip of the SS to the posterior endpoint of the SC along the anterior side of the SS. Method III 11 (Fig. 2E): the SSL (the white solid line) was drawn from the tip of the SS to the middle of the a-d dotted line, which connected the anterior and posterior points where the sclera curved to form the spur.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 A). Schlemm’s canal area (SCA) was drawn and defined as the black area surrounded by the white outline 11 . Schlemm’s canal length (SCL) was measured from the posterior to anterior SC end point by the a-b dotted line 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the SC area (SCA) was significantly associated with the SSL in both POAG and healthy groups. They suggested that the SS plays an important role in the maintenance of SCA and the SSL could be a novel biomarker for POAG evaluation clinically 11 .…”
Section: Introductionmentioning
confidence: 99%